2004
DOI: 10.1016/j.jacc.2004.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Achieved platelet aggregation inhibition after different antiplatelet regimens during percutaneous coronary intervention for ST-segment elevation myocardial infarction

Abstract: Platelet aggregation inhibition in STEMI patients undergoing PCI, treated with antiplatelet agents, is variable and suboptimal for all agents and dosages studied. Only with high-dose tirofiban, mean periprocedural platelet aggregation inhibition exceeded 80%. However, no relationship of platelet aggregation inhibition and angiographic outcome was found in this patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 21 publications
(19 reference statements)
2
61
0
4
Order By: Relevance
“…6,15,17,18,20,21,23,26,28,29 The incidence of minor bleeding at 30 days was 5.5% with GPIs versus 4.1% with control (RR = 1.37; 95% CI, 1.06-1.78; P = 0.016) (Supporting Information Figure 3). No publication bias was detected (Begg's test P = 0.53, Egger's test P = 0.41) and heterogeneity was low (I 2 = 13.5%).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…6,15,17,18,20,21,23,26,28,29 The incidence of minor bleeding at 30 days was 5.5% with GPIs versus 4.1% with control (RR = 1.37; 95% CI, 1.06-1.78; P = 0.016) (Supporting Information Figure 3). No publication bias was detected (Begg's test P = 0.53, Egger's test P = 0.41) and heterogeneity was low (I 2 = 13.5%).…”
Section: Safetymentioning
confidence: 99%
“…6,17,20,21,23,24,28,29 Neither abciximab (RR = 1.99; 95% CI, 0.70-5.68; P = 0.20), nor the small molecule GPIs (RR = 0.98; 95% CI, 0.35-2.74; P = 0.98) were independently associated with thrombocytopenia. Stroke data were available for 5 studies and was not significantly different between GPIs and control (RR = 0.37; 95% CI, 0.13-1.08; P = 0.068).…”
Section: Safetymentioning
confidence: 99%
“…9,10 The study results of Van Werkum et al show striking similarities with a previous study which used the same platelet function test. 11 Again only 46% platelet aggregation inhibition was found in the abciximab group and 86% platelet aggregation inhibition in the high-dose tirofiban group. The explanation for this 'drug resistance' might be related to the dose of the drug or the underlying disease.…”
mentioning
confidence: 91%
“…A conventional dose of tirofiban showed suboptimal periprocedural platelet inhibition in patients with ST-segment elevation myocardial infarction (STEMI). 3 Several recent clinical studies demonstrated that the use of high-dose bolus tirofiban is safe and improves angiographic and clinical outcomes in patients undergoing high risk PCI. 4 The timing of administration of GP IIb/IIIa inhibitors is also an issue.…”
mentioning
confidence: 99%